2012
DOI: 10.1590/s0100-204x2012000600012
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial bacterial strains on Agaricus blazei cultivation

Abstract: -The objective of this work was to evaluate the effects of six bacterial strains isolated from Agaricus blazei (ABM) on its cultivation. The six strains were characterized as to their effects on the productivity, polysaccharide-protein complex (PSPC), and polysaccharide contents of ABM cultured on sterilized casing soils. Three isolates enhanced ABM mycelium growth. Inoculation of Arthrobacter sp. or Exiguobacterium sp. on sterile peat casing soil resulted in 64% increase in ABM mushroom total fresh matter yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The physicochemical properties of the culture medium and loamy casing soil were previously described in Young et al (2012) and are summarized in Table 1. The casing soil was soaked in sterile water at a ratio of 1:1 (w/w) and shook for 0.5 hour at 25 o C. Aliquots (100 ml) of the soil solution were plated on nutrient agar (HiMedia Laboratories, Mumbai, India) by the serial dilution method, and incubated at 25 o C for three days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physicochemical properties of the culture medium and loamy casing soil were previously described in Young et al (2012) and are summarized in Table 1. The casing soil was soaked in sterile water at a ratio of 1:1 (w/w) and shook for 0.5 hour at 25 o C. Aliquots (100 ml) of the soil solution were plated on nutrient agar (HiMedia Laboratories, Mumbai, India) by the serial dilution method, and incubated at 25 o C for three days.…”
Section: Methodsmentioning
confidence: 99%
“…Amplification was set at the following conditions: 95 o C for 5 min, followed by 35 cycles of 95 o C for 1 min, 60 o C for 1 min, 72 o C for 2 min, and final extension at 72 o C for 7 min. DNA fragments of approximately 1,500 bp were purified using a QIAquick Gel Extraction Kit (Qiagen, Hilden, Germany) and were sequenced as described in Young et al (2012). The cycle sequencing primers used were: 3F: 5'-CCTACGGGAGGCAGCAG-3', 4R: 5'-TTA CCGCGGCTGCTGGCAC-3', and 5F: 5'-AAACTC AAATGAATTGACGGGG-3' (Edwards et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For A. subrufescens cultivation, the use of inoculants on casing layer has been reported (Young et al, 2012) but the present work is the first to report the utilization of inoculants for the composting process aiming a simpler technology which may be apropriate for small mushroom growers in developing countries.…”
Section: Resultsmentioning
confidence: 87%
“…It has been reported that Ochrobactrum pseudogrignonense is able to induce and increase mushroom growth of Pleurotus ostreatus with significant increasing yield (Maryana and Aryantha 2013). Young et al (2012) found six soil bacterial strain that increases Agaricus blazei growth. Studies regarding biogical factors such as induction by indigenous MGPB are rarely done.…”
mentioning
confidence: 99%